Opioid-free anaesthesia using continuous dexmedetomidine and lignocaine infusion in elective spine surgery and its effect on patient recovery at a referral neuroscience hospital, Dhaka - Mamun, M. Anwarul; Reza Rony, M. Rayhan; Rahman, Mohammed Mohidur; Rahman Tannee, Tanjila; Islam, M. Rabiul; Ferdous, Jannath Ara; Rahman, Dawan Mohammad Anisur (International Journal of Research in Medical Sciences, 2026)
Background: Opioid anaesthesia, though useful in pain control in spine surgery, is associated with adverse effects like respiratory depression, nausea, and vomiting after the surgery, and slow recovery. Opioid-free anaesthesia with dexmedetomidine and lignocaine has been an emerging prospect to improve perioperative care with the elimination of opioid-induced complications. Methods: This prospective observational study was done among 60 ASA I-III patients aged 18-65 years having elective spine surgery in a referral neuroscience hospital in Dhaka. Anaesthesia was induced with dexmedetomidine (1 μg/kg for 10 min), lignocaine (1.5 mg/kg), propofol (2 mg/kg), and rocuronium for relaxation. Maintenance was by continuous infusion of dexmedetomidine (0.4-0.7 μg/kg/h) and lignocaine (1-2 mg/kg/h), topped up by sevoflurane and non-opioid analgesics. Outcome variables were hemodynamic stability, postoperative pain score, opioid consumption, recovery parameters, and complications. Results: 100% of patients were hemodynamically stable during intraoperative time without MAP or heart rate variability ≥20% from baseline. No hypotension or bradycardia intervention was required. Postoperatively, 63.3% of patients experienced mild pain (VAS 0-3), and 15% required rescue opioids. Early extubation (≤10 minutes) succeeded in 93.3% of patients, 56.7% of patients had ≤12 hours of ICU stay, and 46.7% were discharged within 3 days. PONV occurred in only 10% of the patients, without any respiratory depression. Hemodynamic stability showed moderate negative correlations with extubation time (r=-0.34, p=0.01), ICU stay (r=-0.29, p=0.03), and rescue opioid requirement (r=-0.36, p=0.008). Conclusions: Opioid-free anaesthesia with continuous infusion of dexmedetomidine and lignocaine offers excellent hemodynamic stability, analgesia, and recovery profile for elective spine surgery with minimal side effects, being safe and effective as compared to traditional opioid-based techniques.